Pulmonary function tests in extremely low gestational age infants at one year of age. Issue 2 (23rd November 2021) - Voynow, Judith A.; Feng, Rui; Ren, Clement L.; Dylag, Andrew M.; Kemp, James S.; McDowell, Karen; Sharp, Jack; Moore, Paul E.; Eichenwald, Eric; Panitch, Howard; Clem, Charles; Johnson, Robin; et al.
Abstract: Rationale: Identifying neonatal and post‐discharge exposures among extremely low gestational age newborns (ELGANs) that drive increased pulmonary morbidity and abnormal lung function at 1 year of age proves challenging. Objective: The NIH‐sponsored Prematurity and Respiratory Outcomes Program (PROP), evaluated infant pulmonary function tests (iPFTs) at 1 year corrected age to determine which demographic and clinical factors are associated with abnormal lung function. Methods: iPFTs were performed on a PROP subcohort of 135 participants following Institutional Review Board (IRB)‐approved written consent. Demographic data, Neonatal Intensive Care Unit (NICU) clinical care, and post‐NICU exposures were analyzed for association with iPFTs. Main Results: A significant decrease in forced expiratory volume at 0.5 s (FEV0.5 ) and/or forced expiratory flows at 75% of forced vital capacity (FEF75 ), were associated with male sex and African American race. Clinical factors including longer duration of ventilatory support, exposure to systemic steroids, and weight less than the 10th percentile at 36 weeks postmenstrual age were also associated with airflow obstruction, whereas supplemental oxygen requirement and bronchopulmonary dysplasia were not. Additionally, the need for respiratory medications, technology, or hospitalizations during the first year, ascertained by a quarterly survey, were the only post‐NICU factors associated with decreased FEV0.5 and FEF75 . Only 7% of infants had reversible airflow obstruction. Conclusions: Neonatal demographic factors, respiratory support in the NICU, and a history of greater post‐NICU medical utilization for respiratory disease had the strongest association with lower lung function at 1 year in ELGANs.